Gambaran Pemberdayaan Masyarakat oleh Komunitas Pemuda Pambangun Nagari - Ilsadul Ilbat; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is backgrounded by developing process of Teletabis Hill Tourism objects located in Nagari Lubuak Layang, South Rao District, Pasaman Regency. This was allegedly due to community empowerment activities conducted by Pambangun Nagari Youth Community. The aims of the research is describe the community empowering process, strengthening potention, and autonomyc of community in Nagari Lubuak Layang, Pasaman Regency. The quantitative approach and descriptive design was used in this research. The population of this research is 40 people who lived around the tourism village. The sample was obtained using 33 random sampling techniques. The data collection techniques were questionnaires, and data analysis used percentage formula. The results of this research showed that: (1) community empowerment in enabling community activities was conducted very well; (2) community empowerment in strengthening activities was conducted very well; and (3) community empowerment in the autonomyc activities of the community is well done. This research suggest that: (1) the community could maintained and enhanced tourism development activities for giving more effective impact on community empowerment; and (2)  the community could conserving the tourism objects for giving good influence on the progress of community.Keywords: Education, Empowerment, Autonomyc, Community